Common Running Overuse Injuries and Prevention - Žiga Kozinc; Nejc Sarabon (Montenegrin Sports Academy, 2017)
Runners are particularly prone to developing overuse injuries. The most common running-related injuries include medial tibial stress syndrome, Achilles tendinopathy, plantar fasciitis, patellar tendinopathy, iliotibial band syndrome, tibial stress fractures, and patellofemoral pain syndrome. Two of the most significant risk factors appear to be injury history and weekly distance. Several trials have successfully identified biomechanical risk factors for specific injuries, with increased ground reaction forces, excessive foot pronation, hip internal rotation and hip adduction during stance phase being mentioned most often. However, evidence on interventions for lowering injury risk is limited, especially regarding exercise-based interventions. Biofeedback training for lowering ground reaction forces is one of the few methods proven to be effective. It seems that the best way to approach running injury prevention is through individualized treatment. Each athlete should be assessed separately and scanned for risk factors, which should be then addressed with specific exercises. This review provides an overview of most common running-related injuries, with a particular focus on risk factors, and emphasizes the problems encountered in preventing running-related injuries.